STUDI ANALISIS HUKUM ISLAM TERHADAP BUDAYA TOLERANSI ANTAR UMAT BERAGAMA DI PESANTREN TEBUIRENG JOMBANG - Syukron Makmun (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2016)
Since the early days of boarding Tebuireng founded, the educational curriculum and teaching have taught tolerance to all types of people. Included in the attitude of people of different religious beliefs. In this study it was found that building a culture of religious tolerance in Pesantren Tebuireng already built for generations of predecessors. A form of tolerance that such form of cooperation in the field of social and inter-religious dialogue, both formal and informal, and provide security protection facilities. This is based on the mission of Islam as a religion rahmatan lil Alamin. Tolerance as part of a strategy of struggle grounding moral values of Islam, be inclusive in a frame nationality, promoting the values of humanism to interact with non-Muslims. Tolerance in Pesantren Tebuireng not contrary to shariah Islamic law based on a comprehensive knowledge of religion then integrate with the awareness of the interests of the nation in general.Keyword : Pesantren Tebuireng, tolerance, humanisme.